An investigation of the challenges experienced on the development of listening and speaking skills : a case of two selected high schools in Mahwelereng Circuit, Limpopo Province - Nchabeleng, Bonolo Koruakae (My University, 2022)
We live in a world in which communication plays a very crucial role in everything we engage in. The fact that the new Constitution of South Africa (Act No.200 of 1993) has given official status to the 11 major languages (something which was formerly granted only to English and Afrikaans) is irrefutable. In spite of all that, the English language has remained a major national language, as well as a Medium of Instruction in schools and universities in South Africa. However, effective communication has since been one of the most critical concerns in South Africa because English has been labelled as a nightmare. This is because the majority of learners at schools experience difficulties in acquiring Communicative Competence Skills in English, which is their Second Language (SL).The reality is, for one to communicate effectively, an individual should acquire Communicative Competence, which will enable him to engage with other people. To tackle this problem, there are effective and efficient strategies that need to be addressed. Literature reviews point out (a) the importance of the English First Additional Language (EFAL); (b) the challenges learners face at schools in acquiring Communicative Competence in English Second Language (ESL); and(c) solutions to overcome this situation. This study aimed at investigating the challenges experienced on the development of listening and speaking in EFAL. The study employed a qualitative Case Study design to investigate the challenges experienced on the development of listening and speaking in EFAL. Data for this qualitative case were obtained from interviews with learners and teachers. Observations were made at the two selected schools, and questionnaires were administered as well. The findings revealed various challenges that impede learners from developing Communicative Competence Skills in ESL. Learners do not understand English because their vocabulary in the language is limited. They also have challenges in pronouncing English words, and they cannot express themselves accurately in ESL because it is not their home language. Consequently, their proficiency in the language is low and impinges on their comprehension levels. It is recommended that teachers should ensure that they create a beneficial environment for learners to acquire Communicative Competence. Teachers should, in addition, introduce activities which will enable learners to communicate frequently. Learners should be given opportunities where they can read frequently, because reading improves vocabulary and helps one to become familiar with sentence structure, word order and correct pronunciations. Furthermore, learners should invest in a good dictionary to check unfamiliar words. Learners should build active listening and speaking skills that improve lines of communication with others and should be aware of their own communication barriers. They should learn different phrases/strategies that improve how they respond, and they should not fear to be offended. They should, furthermore, feel comfortable when they express their emotions and look at the speaker directly when communicating. Most importantly, learners should put aside distracting thoughts and should also listen to the speaker’s body language
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2022
Keywords: Communicative Competence; Listening and Speaking; Challenges; Communicative competence in children; English language -- Study and teaching (Elementary); Listening -- Ability testing